INFLUENCE OF THE FILLER METAL IN WELDED POINTS OF DUPLEX STAINLESS STEELS - Roldan C., Edmundo; Hernandez A., Juan; Salinas R., Eleazar; Cerecedo S., Eduardo; Rodriguez L., Ventura (European Scientific Journal, ESJ, 2014)
The aim of this work was to study the effect of welding with ER2209 filler metal and its effectiveness, to be used in â€œButtâ€ and â€œTâ€ unions in a UR2202 stainless steel with a thickness of 8 mm, and in a 201LN2B stainless steel with a thickness of 5 mm, using the welding process of Gas Metal Arc Welding (GMAW), with a 97% Argon â€“ 2.5 % CO2 gas protection by means of a pulsed arc transfer. Hardness of this material shows a decreasing going from 21.2 to 30.8 Rockwell G in the â€œTâ€ samples and from 27.1 to 37.2 Rockwell G for â€œButtâ€ samples, whereby the distortion caused by the welding process is minimal. In the same way, these welds showed micro structures with perlite and ferrite phases in welding cords. Mechanical properties due to hardness tests also were determined.